PENGARUH AKTIVITAS PENDIDIKAN JASMANI DI PAGI DAN SIANG HARI TERHADAP HASIL BELAJAR KETERAMPILAN BOLA BASKET DI MTS SUNAN KALIJAGA SIWULUH KABUPATEN BREBES TAHUN PELAJARAN 2011/2012 - Zakiyatul Fitri, - (2012)
Physical education activities in the morning and afternoon has advantages and disadvantages of each so it is difficult to determine which is more time effective to achieve a successful learning skills, because the writer wanted to prove the extent to which differences in execution time penjas activity affects the success of learning basketball skills in school. The goal is to determine how much difference the influence of physical education activities in the morning and afternoon to successful learning basketball skills in Mts Sunan Kalijaga Siwuluh. The research method used was experimental method. Sampling was done by purposive sampling / sample aims, the students were 60 male students were divided into 2 groups: 30 students and 30 students in the morning the afternoon group. In the morning the group pre-test measurement results of his 48.36 average standard deviation of 7.60 while the post test results mean 56.83 and standard deviation of 7.79. Group during the average pre-test results of 43.16 and a standard deviation of 7.08 while the post test results mean 45.99 and standard deviation of 7.95. The results of tests on the morning increase in the standard deviation of 5.74 and 6.97 during the group average increase is 4.34 standard deviation of 4.62. For df = 59 obtained values of 2.00 t table. Because t-hitung smaller than t-tabel (0.16 <2.00) t = 0.43 is greater than α = 0.05 and then H-0 accepted, meaning that there is no significant difference. Can be concluded that there is no difference in the effect of time on the activity of basketball skills learning outcomes in students the morning and afternoon groups.